119k views
1 vote
I need help to do these composition of functions. I have a photo if needed.h(a)=a^2-5ag(a)=3a+1Find (h • g)(-2)

User Kaediil
by
4.6k points

1 Answer

2 votes

Solution:

Let the following functions:


h(a)=a^2-5a

and


g(a)\text{ = 3a+1}

notice that the composition of the above function is :


(h\circ g)(a)=h(g(a))=h(3a+1)=(3a+1)^2-5(3a+1)

this is equivalent to:


(h\circ g)(a)=(3a+1)^2-5(3a+1)=(3a)^2+2(3a)+1\text{ -15a-5}

this is equivalent to:


(h\circ g)(a)=9a^2+6a+1\text{ -15a-5}

putting together the similar terms, we get:


(h\circ g)(a)=9a^2-9\text{a}-4

now, replacing a = -2 in the above equation, we get:


(h\circ g)(-2)=9(4)^{}-9(-2)-4=\text{ 36+18-4 = 50}

then, we can conclude that the correct answer is:


(h\circ g)(-2)\text{ = 50}

User Shabany
by
4.0k points